Audit on the Recommendation of Exercise by Clinicians in a Community Mental Health Team - Cissy Atwine; Joe Parvin; Sally Axelby; Isabelle Akin-Ojo (BJPsych Open)
Aims: Determine the proportion of patients who have exercise documented as part of their initial treatment plan. Identify any trends in exercise recommendations across different mental health conditions. Highlight areas for improvement and develop strategies to increase the incorporation of exercise recommendations in clinical practice.